Antibiotic Sensitivity Pattern of Staphylococcus aureus and Escherichia coli Isolated from Bovine Fresh Milk (POLA SENSITIVITAS ANTIBIOTIK TERHADAP STAPHYLOCOCCUS AUREUS DAN ESCHERICHIA COLI YANG DIISOLASI DARI SUSU SAPI SEGAR) - Muslimin, Lucia Ratna Winata; Nainu, Firzan; Himawan, Rochmat (Jurnal Veteriner; Vol 16 No 4 (2015), 2016)
The aims of this study were to determine the sensitivity of S.aureus and E. coli isolated fromfresh milk against against several antibiotics and to determine the safety of the milk for humancomsumsion. Milk was collected from milking diary cow and was used for the bacterial isolation. E.coli were were identified using Total Plate Count (TPC), Gram staining, their growth on Endo Agarand Eosin MethyleneBlue Agar, Biochemical analysis including glucose, lactose, sucrose,maltose, andsorbitol would be followed by Sorbitol Mac Conkey Agar Test for the identification of E.coliO157:H7.The isolation and identification of S.aureus were performed using Gram stain, TPC, growth on BairdParker Agar and Mannitol Salt Agar. S. aureus and S. epidermidis were differentiated by coagulaseand catalase tests. The antibiotic sensitivity tests for both S. aureus and E.coli were carried out usingthe following antibiotics: ampicillin, bacitracin, vancomycin, cefoperazone, ceftriaxone, cefotamine,cefuroxime, cefepime, cefazoline, ceftazidime, chloramphenicol, tetracycline, doxycycline, amikacin,kanamycin, neomycin, ertapenem, meropenem, imipenem, erythromycin, gentamycin, nalidixic acid,ciprofloxacin, levofloxacine, norfloxacine, ofloxacin, and novobiocin. Fresh milk obtained from thefarm was positive for S.aureus and E.coli and resistant to most antibiotics tested. The best antibioticsfor S. aureus were imipenem (54.1 mm), ampicillin (42.3 mm), cefazolin (41.6 mm), doxycycline (41.15mm), and for E.coli were Imipenem (30.1 mm), ertapenem (29.5 mm), and meropenem (25.35 mm). Thebovine fresh milk examined was contaminated by S.aureus and E.coli and to some extent, were alsoresistant to most antibiotics tested.
Keywords: antibiotics; sensitivity; E.coli; S.aureus